Analisis Pemilihan Moda Transportasi Mahasiswa Universitas Jember Menuju Kampus - Alfin Kristyanto; Akhmad Hasanuddin; Paksitya Purnama Putra (Universitas Islam 45, 2022)
The use of private transportation modes to the Tegal Boto campus, Jember University has increased. The increase in the volume of private vehicles will cause congestion if it is not regulated properly. Therefore, an analysis related to the selection of student transportation modes is needed to determine the tendency of students to choose transportation modes. The results of this study will be used as a first step in the improvement of transportation facilities in the area around the Tegal Boto campus, Universitas Jember. Analysis of the factors that influence students in choosing the mode of transportation will be carried out in this study. In addition, the priority of choosing the mode of transportation used by students to the Tegal Boto campus, Jember University will also be known. Research data will be obtained from questionnaires and documents from the University of Jember. The data will be analyzed using the Analytical Hierarchy Process (AHP). The results of the AHP analysis show that the factors that dominate the choice of student transportation modes to the Tegal Boto campus, Jember University are the time factor (33%). Meanwhile, the student's priority modes of transportation are motorbikes (32.7%). The choice of motorcycle mode has the largest percentage due to it is based on consideration of the time factor. Students need transportation modes that have high flexibility such as motorbikes so that the time needed to reach campus is shorter.